Effects of replacing soybean meal with dried distillers grains with solubles on Boer goat performance and carcass characteristics - Harr, Keayla M.; Crane, Alison R.; Lattimer, James M.; Jones, Cassandra K. (My University, 2018)
United States goat production has expanded over the past decade by almost 2-fold and a significant portion of red meat consumption around the world is goat meat. With the added expansion there has come the push to feed goats a cost-effective diet that increases performance and does not hinder carcass characteristics. There is very limited data available in feeding dried distillers grains with solubles (DDGS) to goats. Feeding DDGS instead of the traditional soybean meal (SBM) in feed rations offers a per protein unit cost advantage of $1.86, which leads to significant cost savings for producers. Therefore, the objective of this experiment was to evaluate if DDGS could be included in place of SBM in a Boer goat diet. Forty-eight Boer goat kids (approximately 70 days of age) were used in a completely randomized design. Goats were housed at the KSU Sheep and Meat Goat Center with 3 kids per pen (4 pens per treatment). Kids were allotted into one of four experimental diets: 1) 0% SBM replaced by DDGS; 2) 33% SBM replaced by DDGS; 3) 66% SBM replaced by DDGS; and 4) 100% SBM replaced by DDGS. All diets were pelleted at the Kansas State University feed mill, with pellets containing roughage, so no supplemental forage was needed. Diets were fed for 47 days with a 14 day step up period. ADG, ADFI, and G:F were calculated every week. At the completion of the experiment, two kids per pen were slaughtered with carcass data collected, including HCW, yield, loin eye area, and fat depth at the 13th rib. Finally, growth and carcass results were analyzed using the GLIMMIX procedure of SAS with pen being the experimental unit and 0.05 as the alpha value. There was no statistical difference (P > 0.05) in HCW, carcass yield, loin eye area, loin eye depth, backfat depth, body wall thickness, BW, or ADFI, indicating no effect of substituting DDGS for SBM. Goats fed DDGS had greater (P < 0.05) G:F than those fed only SBM. While not significant (P > 0.10) goats fed DDGS had a nearly 1 kg greater HCW than those fed the control diet, which could lead to greater profit margins for producers.
Keywords: Spring 2018